Rancang Bangun Antena Mikrostrip Bowtie Pada Frekuensi 5,2 Ghz - Aprinal Adila Asril; Lifwarda Lifwarda; Yul antonisfia (Elektron : Jurnal Ilmiah, 2018)
Microstrip antennas are very concerned shapes and sizes. Can be viewed in terms of simple materials, shapes, sizes and dimensions smaller antennae, the price of production is cheaper and able to provide a reasonably good performance, in addition to having many advantages, the microstrip antenna also has its drawbacks one of which is a narrow bandwidth. In this research will be designed a microstrip antenna bowtie which works at a frequency of 5.2 GHz which has a size of 68mm x 33mm groundplane. For the length and width of 33mm x 13mm patch. This antenna is designed on a printed cicuit board (PCB) FR4 epoxy with a dielectric constant of 4.7 and has a thickness of 1,6mm. This bowtie microstrip antenna design using IE3D software. This antenna has been simulated using IE3D software showed its resonance frequency is 5.270 GHz with a return loss -23 595 dB bandwidth of 230 MHz, VSWR 1,142, unidirectional radiation pattern and impedance 43,919Ω. The results of which have been successfully fabricated antenna with a resonant frequency of 5.21 GHz with a return loss -16.813 dB bandwidth of 79 MHz, VSWR 1.368, unidirectional radiation pattern, impedance 43,546Ω and HPBW 105 °.